Hometown Investment Trust Funds A Stable Way to Supply Risk Capital - Yoshino, Naoyuki; Kaji, Sahoko; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2013)
This book records the first success stories of a new form of financial intermediation, the hometown investment fund, that has become a national strategy in Japan, partly to meet the need to finance small and medium-sized enterprises (SMEs) after the devastating earthquake and tsunami in March 2011. The hometown investment fund has three main advantages. First, it contributes to financial market stability by lowering information asymmetry. Individual households and firms have direct access to information about the borrowing firms, mainly SMEs, that they lend to. Second, it is a stable source of risk capital. The fund is project driven. Firms and households decide to invest by getting to know the borrowers and their projects. In this way the fund distributes risk but not so that it renders risk intractable, which was the problem with the (3z(Boriginate and distribute(3y (Bmodel. Third, it contributes to economic recovery by connecting firms and households with SMEs that are worthy of their support. It also creates employment opportunities, at the SMEs as well as for the pool of retirees from financial institutions who can help assess the projects. Introduction of the hometown investment fund has huge global implications. The world is seeking a method of financial intermediation that minimizes information asymmetry, distributes risk without making it opaque, and contributes to economic recovery. Funds similar to Japan$1 (Bs hometown investment fund can succeed in all three ways. After all, the majority of the world$1 (Bs businesses are SMEs. The first chapter explains the theory behind this method, and the following chapters relate success stories from Japan and other parts of Asia. This book should encourage policymakers, economists, lenders, and borrowers, especially in developing countries, to adopt this new form of financial intermediation, thus contributing to global economic stability.s
Keywords: Economics; Finance; Entrepreneurship; Economics/Management Science; Public Finance & Economics; Finance/Investment/Banking.; Financial Economics; Entrepreneurship; Non-Profit Enterprises/Corporate Social Responsibility